Pelatihan Pembuatan & Penggunaan Lembar Kerja Peserta Didik (LKPD) Berbasis Literasi Sains Bagi Guru - Syam, Andi Nurannisa; Rosmini, Rosmini; Rizalia, Syarif; Sukmawati, Sukmawati; Wuriani, Endang (Universitas Bunda Mulia, 2024)
This Community Service (CS) activity aims to: 1) interpret the competencies possessed by South Konawe MIN 2 teachers in making Student Worksheets (LKPD) so far; 2) increase the ability of South Konawe MIN 2 teachers in designing scientific literacy-based LKPD; and 3) train MIN 2 South Konawe teachers to apply scientific literacy-based LKPD in learning activities. All MIN 2 South Konawe teachers were the target participants for this PkM, which took place on October 7 and 8, 2023. This PkM uses the Community-Based Participatory Research (CBPR) method. The results of the PkM show that: 1) South Konawe MIN 2 teachers do not yet have good competence in making LKPD based on scientific literacy, so ongoing training is needed to maximize this competency, as evidenced by the competency in deepening scientific literacy material by 25% and competence in deepening LKPD material. amounting to 41.91%; 2) South Konawe MIN 2 teachers have successfully created scientific literacy-based LKPD through training and mentoring, as evidenced by the link https://bit.ly/ANS1-PkM-Litapdimas-2023; 3) These teachers have successfully implemented scientific literacy-based LKPD in learning activities through training and mentoring, as evidenced by the link https://bit.ly/ANS2-PkM-Litapdimas-2023.